DIGITAL LEARNING AND TEACHING TECHNOLOGY IN CURRICULUM PRACTICE IN JIANGXI, CHINA - Hu , Shuoli; Hussin, Hanipah; Zhou, Jiawei (Journal of Human Capital Development (JHCD), 2025)
ABSTRACT This study explores the implementation of digital learning and teaching technologies in the new curriculum practice in Jiangxi Province, China. The arrival of digital technologies has transformed traditional educational practices worldwide, and China has made significant strides in integrating digital tools and resources into its education system. Research methodology use is explanatory research design, incorporating both quantitative and qualitative data collection where sample of teachers (200) and students (200) from Nanchang Institute of Technology involved. The quantitative phase involves surveys and assessments to measure the extent of digital learning and teaching technology. and teacher effectiveness. The qualitative phase includes interviews and observations to gain a deeper understanding of the challenges, opportunities, and perceptions surrounding digital learning and teaching in the new curriculum practice. The findings of this study have significant implications for educational policymakers, school administrators, teachers, and students. By exploring the current state of digital learning and teaching in the new curriculum practice, the study contributes to the existing literature on educational technology in China and provides insights into effective strategies for leveraging digital technologies to enhance teaching and learning outcomes. The research outcomes can be used to inform the development of evidence-based policies and practices that optimize the integration of digital tools and resources into the education system, ultimately improving the educational experience and outcomes for students in Jiangxi Province and similar contexts. Keywords: digital learning; teaching technology; curriculum practice; educational policy